MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS DENGAN MENGGUNAKAN STRATEGI ACTION LEARNING PADA MAHASISWA KESEHATAN MASYARAKAT DI INSTITUT KESEHATAN DELI HUSADA DELI TUA - GINTING, SULASTRI; Hariati, Hariati (Jurnal Kajian Kesehatan Masyarakat, 2019)
The aim of this study is to improving the students’ speaking skill in English Spesific Purposes by using action learning strategy. This research was conducted by using Classroom Action Research (CAR). The subject of this study is college students of Public Health students in third semester which consisted of 48 students. The objective of this research was to improve students speaking English skill by using Action Learning strategy at Third Semester Students of Public Health at Institut Kesehatan Deli Husada Deli Tua. This research was conducted in two cycles which each consists’ of planning, acting, observing, and reflecting. The data were gathered through quantitative and qualitative data. The result of this study showed that there was increasing of students in speaking skill by usingaction learning strategy than Traditional Strategy. The mean of pre-test was 60. The mean of post-test 1 was 76.05. The mean of post-test 2 was 83.22. It means that the scores and the mean in second cycle were better than the first cycle$. The percentage of students who got point >75 also grew up. In the pre-Test, the students who got point >75 up were 4 students (9.09%). In the post-test of cycle 1 students who got point >70 up were 30 students (68.18%). The post-test of cycle 2, students who got point >75 were 38 students (86.36%)$. The conclusion based on data above the students’ speaking ability improved by using action Learning Strategy that can be proved by value in speaking improved in the first meeting to the next meeting.